Monitoring of an effluent treatment plant tested by a plastic recycling company in the municipality of Caçador, Santa Catarina, Brazil - Campos, Roger Francisco Ferreira de; Borga, Tiago; Vazquez, Eric Marcos (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
The pollution of water resources is one of the main environmental problems, since its contamination can be diffuse, linear and punctual, necessitating a management of the sources with power of water pollution. In view of the above, this work aims to develop the monitoring of an effluent treatment plant from chemical-physical analysis in a plastic recycling company of the municipality of Caçador/SC, seeking to analyze its efficiency and interaction with the receiving body . The monitoring was carried out in 2014, 2015 and 2016, through analysis of pH, BOD, COD, Total and Sedimentable Solids, Ammoniacal Nitrogen, Oils and Mineral Greases and Animal Fats. The study shows that the treatment system is not in compliance with the relevant legislation for the BOD parameter and Sedimentable Solids. Thus, the effluent treatment station of the study needs a readjustment of its system, seeking the use of a chemical treatment system and others that decrease the amount of solids of the treated effluent, since the solids are dissolved or total is one of the Major pollutants of water bodies.